Monitoring of XRN4 Targets Reveals the Importance of Cotranslational Decay during Arabidopsis Development . Issue 3 (9th September 2020) - Carpentier, Marie-Christine; Deragon, Jean-Marc; Jean, Viviane; Be, Seng Hour Vichet; Bousquet-Antonelli, Cécile; Merret, Rémy
Abstract : 5′ to 3′ cotranslational mRNA decay is dynamically regulated during Arabidopsis seedling development and fine-tunes translation efficiency. Abstract: RNA turnover is a general process that maintains appropriate mRNA abundance at the posttranscriptional level. Although long thought to be antagonistic to translation, discovery of the 5ʹ to 3ʹ cotranslational mRNA decay pathway demonstrated that both processes are intertwined. Cotranslational mRNA decay globally shapes the transcriptome in different organisms and in response to stress; however, the dynamics of this process during plant development is poorly understood. In this study, we used a multiomics approach to reveal the global landscape of cotranslational mRNA decay during Arabidopsis ( Arabidopsis thaliana ) seedling development. We demonstrated that cotranslational mRNA decay is regulated by developmental cues. Using the EXORIBONUCLEASE4 (XRN4) loss-of-function mutant, we showed that XRN4 poly(A + ) mRNA targets are largely subject to cotranslational decay during plant development. As cotranslational mRNA decay is interconnected with translation, we also assessed its role in translation efficiency. We discovered that clusters of transcripts were specifically subjected to cotranslational decay in a developmental-dependent manner to modulate their translation efficiency. Our approach allowed the determination of a cotranslational decay efficiency that could be an alternative to other methods to assess transcript translation efficiency. Thus, our results demonstrate the prevalence of cotranslational mRNA decay in plant development and its role in translational control.